Smart leader di era revolusi industri 4.0 - Triyono Arief Wahyudi; Ferryal Abadi; Donant Alananto Iskandar (LPMP Imperium, 2024)
Significant transformations have taken place with regards to the way products are produced thanks to manufacturing digitization. This transition is so convincing that it is called Industry 4.0 to represent the fourth revolution that has taken place in manufacturing. From the first industrial revolution (mechanization through hydro and steam power) to mass production and assembly lines using electricity in the second revolution, the fourth industrial revolution will take what started in the third with the adoption of computers and automation and enhance it with intelligent and autonomous systems driven by data and machine learning. The research aims to address leadership styles that are influenced by rapid technological developments by changing traditional leadership styles to digital leadership. A smart leader has the ability to inspire his employees to innovate and defend ideas. An acumen in implementing smart leadership benchmarks demonstrates a fast, cross-hierarchical, cooperative, and team-oriented approach that integrates innovation frequently.